2012
DOI: 10.4067/s0718-16202012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of Japanese plum cultivars (Prunus salicina) using SSR and ISSR molecular markers

Abstract: B. Carrasco, C. Díaz, M. Moya, M. Gebauer and R. García-González. 2012. Genetic characterization of Japanese plum cultivars (Prunus salicina) using SSR and ISSR molecular markers. Cien. Inv. Agr. 39(3): 533-543. The genetic characterization of 29 elite Japanese plum cultivars (Prunus salicina) and 4 Prunus cultivars was carried out by analyzing 97 Simple Sequence Repeat (SSR) alleles and 232 binary Inter Simple Sequence Repeat (ISSR) loci. A high level of genetic variability was found for these two molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
4
21
4
Order By: Relevance
“…In this study, we detected high levels of diversity within 14 different plum landraces from the PRD region that have been selected through the years by local growers. The diversity indexes were lower than those described by Carrasco et al [14] (He = 0.80 and Ho = 0.90) and Ferrero Klabunde et al [15] (PIC = 0.80 and Ho = 0.77) with eight SSR markers. However, this was expected due to a higher number of P. salicina cultivars analyzed (29 and 47, respectively).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In this study, we detected high levels of diversity within 14 different plum landraces from the PRD region that have been selected through the years by local growers. The diversity indexes were lower than those described by Carrasco et al [14] (He = 0.80 and Ho = 0.90) and Ferrero Klabunde et al [15] (PIC = 0.80 and Ho = 0.77) with eight SSR markers. However, this was expected due to a higher number of P. salicina cultivars analyzed (29 and 47, respectively).…”
Section: Discussioncontrasting
confidence: 71%
“…Mnejja et al [2] isolated 27 microsatellites or simple sequence repeats (SSRs) in P. salicina, whereas Carrasco et al [14] analyzed genetic diversity and correlation among 29 Japanese plum cultivars using a combination of inter simple sequence repeat (ISSR) and SSR markers. On the other hand, Klabunde et al [15] genotyped 47 cultivars with eight microsatellite markers.…”
Section: Introductionmentioning
confidence: 99%
“…The H E value was similar to that obtained for other tropical fruit trees, including mango cultivars and Indian jujube cultivars (Chiou et al, 2012). However, the Ne and H E values of wax apple were noticeably lower than those of Japanese plum cultivars (Carrasco et al, 2012) and apple cultivars (Sikorskaite et al, 2012). Both Japanese plum and apple cultivars have strong self-incompatibility (Okie and Weinberger, 1996;Hegedus, 2006) compared to the wax apple, which is a self-compatible species (Chantaranothai and Parnell, 1994).…”
Section: Resultsmentioning
confidence: 71%
“…According to Wright (1978), values of 0.25 show high genetic differentiation, which may be reflected in the high degree of domestication that these materials have suffered, since most of them are commercial varieties. Carrasco et al, 2012 found an index fixation of F = -0.127, higher than those in other allogamous species such as the almond (F = 0.15; Fathi et al, 2008), and wild apple (F = 0.10; Coart et al, 2003). Excess heterozygosity could be explained by the negative selective mating related to the self-incompatibility system, such that the parental lines carry different favored alleles than the interspecific cross usually used in plum breeding programs.…”
Section: Resultsmentioning
confidence: 91%
“…In the plum, Carrasco et al (2012) molecularly characterized cultivars of the Japanese plum (Prunus salicina), using the molecular markers SSR and ISSR.…”
Section: Resultsmentioning
confidence: 99%